2008
DOI: 10.1038/sj.bjc.6604253
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of splice variants and subcellular localisation of survivin in non-small cell lung cancers

Abstract: Survivin is a member of the inhibitor of apoptosis protein family. Survivin has splice variants with different biological functions associated with tumorigenesis. We investigated 134 non-small cell lung cancers (NSCLCs) to study the clinical significance of wildtype survivin, survivin-2B, and survivin-deltaEx3. Real-time PCR analyses were performed for their gene expressions. The subcellular localisation of survivin proteins was evaluated by immunohistochemistry. The Ki-67 proliferation index and the apoptotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…1,2.24 In fact, some studies in solid tumors have demonstrated that nuclear survivin expression assessed by immunohistochemistry could be considered a favorable prognostic marker. 25 In hematologic malignancies, a differential compartmental localization of survivin has been assessed in mantle cell lymphoma 26 and lymphoid leukemia (acute and chronic) 27 by western blot and immunohistochemical studies. However, to the best of our knowledge only two studies have analyzed the global cellular expression of WT survivin and isoforms by reverse transcriptase polymerase chain reaction analysis in AML 8,28 and this is, therefore, the first description of the distribution of WT survivin and isoforms in nuclear and cytoplasmic compartments.…”
Section: Discussionmentioning
confidence: 99%
“…1,2.24 In fact, some studies in solid tumors have demonstrated that nuclear survivin expression assessed by immunohistochemistry could be considered a favorable prognostic marker. 25 In hematologic malignancies, a differential compartmental localization of survivin has been assessed in mantle cell lymphoma 26 and lymphoid leukemia (acute and chronic) 27 by western blot and immunohistochemical studies. However, to the best of our knowledge only two studies have analyzed the global cellular expression of WT survivin and isoforms by reverse transcriptase polymerase chain reaction analysis in AML 8,28 and this is, therefore, the first description of the distribution of WT survivin and isoforms in nuclear and cytoplasmic compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to clarify the biological significance of the Wnt3 expression in NSCLCs, we investigated the Wnt3 expression in relation to Wnt targets, including c-Myc [9] and survivin [11,12]. In addition, we also evaluated the tumor proliferation rate and tumor apoptosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…At least 200 tumor cells were scored per x40 field. Regarding pansurvivin expression, the nuclear staining and the cytoplasmic staining in each section were evaluated, respectively, in a semi-quantitative manner which reflected both the intensity and percentage of cells staining at each intensity, as reported previously (23). The intensity was classified as 0 (no staining), +1 (weak staining), +2 (distinct staining), or +3 (very strong staining).…”
Section: Methodsmentioning
confidence: 99%
“…The statistical significances of survivin gene expression and protein expression of Wnt1 and Wnt5a in relation to several parameters were assessed by the t-test or the ¯2 test. The sample was classified as a survivin-high tumor when the standardized survivin gene expression was >1.0, because a standardized survivin gene expression cut-off line of 1.0 demonstrated the greatest significance in relation to the apoptotic index and the Ki-67 proliferation index (23). The sample was classified as a Wnt1-high tumor when the percentage of Wnt1-positive tumor cells was >50%, and the sample was classified as a Wnt5a-high tumor when the percentage of Wnt5a-positive tumor cells was >30%, as reported previously (24,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation